HUBUNGAN PENGETAHUAN TENTANG KANKER PAYUDARADENGAN PARTISIPASI WANITA DALAM DETEKSIDINI KANKERPAYUDARA - Chrismis Novalinda Ginting (Universitas Prima Indonesia, 2020)
Breast cancer is a condition in which cells have lost their normal control and mechanisms, resulting in abnormal growth that occurs in breast tissue. How to prevent breast cancer by doing a breast self-examination. Signs and symptoms of breast cancer include a lump in the breast, changes in the breast, nipple discharge, and breast engorgement. The purpose of this study was to determine the relationship between knowledge of breast cancer and women's participation in early detection of breast cancer in the first environment of Tanjung Gusta Village, Medan, which was held on 19-29 June 2019 with a population of 62 people. The sampling technique used a random sampling method. The data collection method in this research is using primary data. The results of this study indicate that the majority of women with sufficient knowledge about breast cancer are as many as 25 people (40.3%) and the minority of women who are knowledgeable enough about 24 people (38.7%), while the mothers who are well informed are 13 people (21.0%). From the results of the study, the number of women who had participated in breast self-examination was as many as 20 (32.3%) and the number of women who had never had their breast check-ups was 41 (67.7%). Based on the results of this study, it was concluded that the knowledge of women about breast cancer was mostly sufficient, while the participation of women in early detection of breast cancer mostly never did breast self-examination.